A Microwave Bridge Method for Measuring the Complex Permittivity of Liquids - Singh S.P.; Jha R.K.; Misra D.K. (My University, 2025)
In this short paper, a microwave bridge method is discussed for measuring the complex permittivity of dielectric materials. The underlying principle of the technique along with the experimental results is presented here. The complex permittivities of benzene, carbon tetrachloride, petrol, and kerosene are illustrated at a few frequencies in X-band. The variation of the dielectric properties of petrol-kerosene mixture is also studied by this method. Copyright © 1981 by The Institute of Electrical and Electronics Engineers, Inc.